Investment in process innovation: Technological obsolescence in Australian manufacturing - Bloch, Harry; Mangano, Maria; Courvisanos, Jerry (2007)
This is an empirical study of investment in process innovation for manufacturing industry. In examining the extent of technological innovation embodied in capital investment, this study identifies the nature technological obsolescence that is implied in this investment process. The empirics are from Australian manufacturing, but the model and the implications are applicable to any advanced capitalist economy. The research begins by identifying technological obsolescence from an approach devised by Wilfred Salter in his analysis of technical change. By defining obsolescence in terms of cost minimisation, Salter provides a method of identifying how and when firms find it profitable to invest in technological innovation embodied in the newest vintage capital equipment. Thus, technological innovation becomes endogenous to the investment process. Technical change in this paper is modelled as affecting the use of each input differently rather than reducing use of all inputs by a uniform proportion. Input-saving estimates calculated for different industries show obsolescence to be identified with the introduction of new equipment that is labour saving. This result enables the inclusion of labour saving as a proxy for technological innovation into an investment model based on the work of Micha Kalecki. With profits as the ability to invest factor, innovation as the inducement, the two factors combine for an explanation of the capitalist accumulation process.